Malaysian federalism: issues and acceptance - Muslim, Nazri; Jalil, Faridah; Musa, Nurhafilah; Mokhtar, Khairil Azmin; Md Khalid, Rasyikah (Australian Academy of Business and Social Sciences (AJSBS), 2015)
After the 2008 General Election, Malaysians were witnessing dynamics of a federal system of government after being ruled by the same coalition parties of Barisan Nasional (National Front) since Independence. When the coalition of Pakatan Rakyat (People’s Front) won five states in the 2008 General Election, many intergovernmental conflicts occurred. Pre-2008, the conflict was confined to family matters such as legal effects of conversion to Islam in a non-Muslim marriage. Post 2008, the federal conflict entered the public law sphere involving a legal tussle between the federal government and the state of Kelantan in the petroleum royalty issue. These federal conflicts have been highlighted in the mass media, catapulting the public from being ignorant about federalism to being curious as to which level of government actually has the power to manage the issues raised. A quantitative study was conducted to find out Malaysians’ level of knowledge, understanding, acceptance and perception towards the federal system in the country. The paper discusses some of the outcomes of the study.